Excesso de peso em estudantes quilombolas e a insegurança alimentar em seus domicílios - Cordeiro, Mariana de Morais (2013)
Introduction: despite the few studies on the profile of health and nutritional status of young quilombolas, one realizes that the urban environment can influence the eating habits of this population, with consequent occurrence of overweight. This situation of nutritional status and dietary pattern in quilombolas communities seems to be a nonsense when it shows the concomitant presence of food insecurity in their homes. Objective: to characterize the nutritional status of students quilombolas and food security in their homes. Methods: A cross-sectional study with 226 students from six to 19 years who attended local schools visited in the period March-August 2012. Information was collected on age, sex, nutritional status, location of the school who were enrolled and applying the Brazilian Scale for Measuring Food Insecurity conducted with the families of the students interviewed. Tests were conducted chi-square association considered significant when p-value presented <0.05. The study was approved by the Ethics Committee of the Universidade Federal de Goiás Results and discussion: food insecurity was present in 75.2% of families quilombolas. There was a higher frequency of overweight (17.2%) compared to the low weight (1.3%) among students. Overweight was more common among students enrolled in urban schools (28.2%) (p <0,05). Conclusions: The presence of overweight concomitant to food and nutrition insecurity allows questioning about new lifestyles and consumption, and even on the poverty profile now present in Brazil. The urbanization of these communities may be an influencing factor in this correlation, which is the reason we suggest new studies to further this discussion.